PROSPECTS OF INTEGRATION OF AQUACULTURE WITH ANIMAL HUSBANDRY AND LAND CROP CULTURE IN TRIPURA STATE - BISWAS, B. K.; ACHARYA, P. (Journal of Indian Fisheries Association, 2015)
Tripura is a densely populated small state with meagre waterresources. 47.51% of the population is constituted by socio-economicallybackward, illiterate, orthodox, tribals and Scheduled Castes. Some of themare nomad and a majority of the rest of the populaiton is refugees fromBangladesh, but almost 100% is fish eater. Settlement of tribals in villages,provision of nutritious food and employment therefore calls for properutilization of every resource they have. The State is poor in waterresources but recently has created 21,636.23 ha of new water area. Tripurais rich in pig population, besides poultry birds. Paddy is the main cropcultivated in arable lands. An integration of live stock raising and landbased agriculture with pisciculture practices around mini barrages willhelp in solving the problems to a great extent. The paper is an attemptto outline the prospects of integration of aquaculture with animalhusbandry and land based crop culture in Tripura State.